2005
DOI: 10.1007/s00442-004-1790-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial diversity and soil functioning affect competition among grasses in experimental microcosms

Abstract: A gradient of microbial diversity in soil was established by inoculating pasteurized soil with microbial populations of different complexity, which were obtained by a combination of soil fumigation and filtering techniques. Four different soil diversity treatments were planted with six different grass species either in monoculture or in polyculture to test how changes of general microbial functions, such as catabolic diversity and nutrient recycling efficiency would affect the performance of the plant communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 38 publications
2
43
0
2
Order By: Relevance
“…This suggests that the consequences of simplified soil community composition and reduced soil diversity may become progressively more inhibiting as time passes. Additionally, because plant diversity is also a driver of ecosystem multifunctionality (3-5, 23), the strong effects of soil organisms on plant diversity, observed here and elsewhere (15)(16)(17)(18)(19)(20), could indirectly influence a number of other ecosystem functions, such as nutrient availability (23) and C sequestration (26). A path analysis indeed indicated that effects of soil biodiversity and composition on measures of nutrient losses were, in part, indirect and mediated by soil biodiversity-induced changes in plant diversity and productivity (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This suggests that the consequences of simplified soil community composition and reduced soil diversity may become progressively more inhibiting as time passes. Additionally, because plant diversity is also a driver of ecosystem multifunctionality (3-5, 23), the strong effects of soil organisms on plant diversity, observed here and elsewhere (15)(16)(17)(18)(19)(20), could indirectly influence a number of other ecosystem functions, such as nutrient availability (23) and C sequestration (26). A path analysis indeed indicated that effects of soil biodiversity and composition on measures of nutrient losses were, in part, indirect and mediated by soil biodiversity-induced changes in plant diversity and productivity (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 53%
“…Litter decomposition was assessed with litterbags containing 15 N-labeled sterilized L. multiflorum shoots that were added to microcosms at the start of the experiment. The ability for a plant to acquire N through the mineralization of its litter is defined here as "N turnover."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the continued use of land for agricultural practices, the soil may be rich in the biological point of view, since many microorganisms found in this environment are considered important in the biological control of diseases and pests of agriculture (Andreoti 2009). Thus, microbial processes play a fundamental importance in the functioning of production systems, performing tasks directly related to their productivity and sustainability (Boncowski and Roy 2005). Rice is a plant of the genus Oryza of the grass family.…”
Section: In Agroecosystemsmentioning
confidence: 99%
“…For example, studies have manipulated the diversity within groups of microorganisms (e.g., bacteria (Bonkowski and Roy, 2005;Griffiths et al, 2000) and mycorrhizal fungi (van der Heijden et al, 1998;Maherali and Klironomos, 2007)), soil mesofauna (e.g., microarthropods; Liiri et al, 2002), and macrofauna (Heemsbergen et al, 2004;Zimmer et al, 2005). Other studies have manipulated the diversity across groups of soil organisms that differ in body size (i.e., microbes, and micro-, meso-, or M.-A.…”
Section: Introductionmentioning
confidence: 99%